Direct Writing of Copper Micropatterns Using Near-Infrared Femtosecond Laser-Pulse-Induced Reduction of Glyoxylic Acid Copper Complex - Mizue Mizoshiri; Keiko Aoyama; Akira Uetsuki; Tomoji Ohishi (Micromachines, 2019)
We have fabricated Cu-based micropatterns in an ambient environment using femtosecond laser direct writing to reduce a glyoxylic acid Cu complex spin-coated onto a glass substrate. To do this, we scanned a train of focused femtosecond laser pulses over the complex film in air, following which the non-irradiated complex was removed by rinsing the substrates with ethanol. A minimum line width of 6.1 µm was obtained at a laser-pulse energy of 0.156 nJ and scanning speeds of 500 and 1000 µm/s. This line width is significantly smaller than that obtained in previous work using a CO2 laser. In addition, the lines are electrically conducting. However, the minimum resistivity of the line pattern was 2.43 × 10−6 Ω·m, which is ~10 times greater than that of the pattern formed using the CO2 laser. An X-ray diffraction analysis suggests that the balance between reduction and re-oxidation of the glyoxylic acid Cu complex determines the nature of the highly reduced Cu patterns in the ambient air.